Respuesta :
The correct answer is y = 11
because:
2y + 7 = 3y − 4
−y + 7 =−4
Subtract 7 from both sides.
−y + 7 − 7 = − 4 − 7
−y = −11
Divide both sides by -1.
y = 11
because:
2y + 7 = 3y − 4
−y + 7 =−4
Subtract 7 from both sides.
−y + 7 − 7 = − 4 − 7
−y = −11
Divide both sides by -1.
y = 11
Answer:
y = 11
Step-by-step explanation:
~Solve~
Let's solve your equation step-by-step.
2y+7=3y−4
Step 1: Subtract 3y from both sides.
2y+7−3y=3y−4−3y
−y+7=−4
Step 2: Subtract 7 from both sides.
−y+7−7=−4−7
−y=−11
Step 3: Divide both sides by -1.
−y
−1
=
−11
−1
y=11
Answer:
y=11